Impact of chronic kidney disease on the prognosis of patients undergoing percutaneous coronary interventions using drug-eluting stents - Kaya, Elif; Cuneo, Alessandro; Hochadel, Matthias; Jünger, Claus Heinrich; Stepper, Wibke; Bramlage, Peter; Kuck, Karl-Heinz; Nienaber, Christoph A.; Senges, Jochen; Eckardt, Lars; Tebbe, Ulrich; Reinecke, Holger (Clinical research in cardiology, 2011)
Chronic kidney disease (CKD) has an adverse impact on survival of patients with coronary artery disease and is associated with poor outcomes after percutaneous coronary intervention (PCI). Although small randomized, controlled clinical trials showed a reduced target vessel revascularization rate and a good safety profile for sirolimus-eluting coronary stents (SES), safety data need to be confirmed in clinical practice. Therefore, the data of the German DES.DE registry were evaluated to obtain acute and long-term data of this high-risk subgroup.